2008
DOI: 10.1038/modpathol.2008.39
|View full text |Cite
|
Sign up to set email alerts
|

Human ASH1 expression in prostate cancer with neuroendocrine differentiation

Abstract: Neuroendocrine differentiation in prostate cancer correlates with overall prognosis and disease progression after androgen-deprivation therapy, although its specific mechanisms are currently poorly understood. A role of Notch pathway has been reported in determining neuroendocrine phenotype of normal and neoplastic tissues. The aim of this study was to analyze whether this pathway might affect neuroendocrine differentiation in prostate cancer. Human achaete-scute homolog 1 (hASH1), a pivotal member of the Notc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 34 publications
1
54
1
Order By: Relevance
“…In this respect, the expression of transcription factors known to drive neuroendocrine differentiation in the embryonic life, such as human achaete-scute-homologue type 1 (hASH1) may be involved in the occurrence of neuroendocrine differentiation [16]. Unfortunately, in the present series, no hASH1 expression was observed (data not shown) suggesting that at least in the intestinal area, the development of neuroendocrine differentiated cells may follow alternative pathways, compared to other models such as the prostate [17].…”
Section: Discussioncontrasting
confidence: 58%
“…In this respect, the expression of transcription factors known to drive neuroendocrine differentiation in the embryonic life, such as human achaete-scute-homologue type 1 (hASH1) may be involved in the occurrence of neuroendocrine differentiation [16]. Unfortunately, in the present series, no hASH1 expression was observed (data not shown) suggesting that at least in the intestinal area, the development of neuroendocrine differentiated cells may follow alternative pathways, compared to other models such as the prostate [17].…”
Section: Discussioncontrasting
confidence: 58%
“…Absent AR expression and disproportional low PSA levels are hallmarks of NEPC [70,71]. NE foci exist within virtually all human prostate adenocarcinomas, reported incidence rates range from 25-90% [67,72,73]. It was suggested that the different morphologic manifestations of NEPC, i.e.…”
Section: Neuroendocrine Prostate Cancermentioning
confidence: 99%
“…NE cells containing neurosecretory granules by electron microscopy, are immunohistochemically detected by positive staining for synaptophysin (SYP) (Figure 1.1A), chromogranins A and B (CHGA, CHGB), neuron-specific enolase (NSE/ENO2), or neuronal cell adhesion molecule (NCAM1/CD56) [67] [68]. NEPC is the most significant histological subtype of PCa compared to other rare categories such as ductal adenocarcinoma, mucinous carcinoma, and signet ring carcinoma [69].…”
Section: Neuroendocrine Prostate Cancermentioning
confidence: 99%
See 2 more Smart Citations